2014
DOI: 10.1007/s11356-014-3238-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum lead and mercury level with cardiometabolic risk factors and liver enzymes in a nationally representative sample of adolescents: the CASPIAN-III study

Abstract: This study aims to determine the difference of serum Pb and Hg levels in adolescents with or without metabolic syndrome (MetS) and the association of serum levels of these heavy metals with cardiometabolic risk factors and liver enzymes in Iranian adolescents. The study population consisted of 320 adolescents (160 with MetS and 160 healthy controls). The relationship between serum heavy metals and cardiometabolic risk factors was assessed by linear regression. The odds ratios (OR) of having metabolic syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 37 publications
7
28
2
Order By: Relevance
“…In Bangladesh, drinking from arsenic contaminated wells was associated with increased ALT [578]. Chronic arsenic exposures were also associated with increased triglycerides in a cross-sectional study [579]; in rats, arsenic increased serum cholesterol, triglycerides, free fatty acids and phospholipids in association with increased oxidative stress and hepatic mitochondrial damage [580] as well as ALT when combined with an obesogenic agent [581, 582]. Lead and mercury exposures were associated with the fatty liver surrogate biomarker, ‘unexplained ALT elevation’ in adult NHANES [561]; and lead, but not mercury, was associated with ALT, plasma triglycerides and LDL, in Iranian adolescents [583].…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…In Bangladesh, drinking from arsenic contaminated wells was associated with increased ALT [578]. Chronic arsenic exposures were also associated with increased triglycerides in a cross-sectional study [579]; in rats, arsenic increased serum cholesterol, triglycerides, free fatty acids and phospholipids in association with increased oxidative stress and hepatic mitochondrial damage [580] as well as ALT when combined with an obesogenic agent [581, 582]. Lead and mercury exposures were associated with the fatty liver surrogate biomarker, ‘unexplained ALT elevation’ in adult NHANES [561]; and lead, but not mercury, was associated with ALT, plasma triglycerides and LDL, in Iranian adolescents [583].…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…A cross-sectional study in people who lived near Minamata, which was highly polluted by methylmercury, reported that the prevalence of liver disease was not significantly higher than other areas with less polluted level of methylmercury [14]. Poursafa et al [15] showed that aspartate aminotransaminase (AST) and alanine aminotransaminase (ALT) did not increase significantly with increased quartiles of blood mercury levels. In contrast, Cave et al [16] suggested a positive association between blood mercury levels and ALT in the US population.…”
Section: Introductionmentioning
confidence: 99%
“…A previous epidemiological study showed that the Minamata area, despite being contaminated with methylmercury, did not have a higher prevalence of liver disease than other areas [ 9 ]. In a study of 320 adolescents, no significant associations were found between blood Hg levels and aspartate aminotransferase (AST) or alanine transaminase (ALT) levels [ 10 ]. Other epidemiological studies in adults and the elderly showed a significant positive association between Hg and AST, ALT, and gamma-glutamyltransferase (GGT) [ 11 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies have mostly analyzed cross-sectional data [ 10 - 12 , 14 ] and did not consider fish consumption as a potential confounder, although fish are a major source of Hg exposure [ 10 , 11 , 13 , 14 ]. In addition, no studies have examined the possibility of a nonlinear relationship between blood Hg and liver function indices, or the possible role of gender.…”
Section: Introductionmentioning
confidence: 99%